Sentiment Analysis of Indonesian Citizen Tweets Using Support Vector Machine on the Rebranding of Twitter to X - Hakim, Bhustomy; Kinasih, Putri Rindu (Universitas Teknokrat Indonesia, 2024)
How other people see the world and assess it affects their opinions, their understanding of it, and the choices they make. As a result, when we need to make a choice, we frequently ask for other people's opinions. Sentiment analysis, also known as opinion mining, is a cost-effective way for businesses and individuals to gather information about public sentiment. In this research, the writers aimed to study Indonesian netizen’s sentiment towards the rebranding of Twitter to X. Obviously, it is impossible to ignore the name and logo changes. The blue and white bird logo on Twitter has become a symbol of the network's culture and lexicon for over ten years. The verb